The Influence of Teacher Performance on Learning Outcome of V-Graders - Suwartini, Sri; Rahmawati, Isna; Ferryka, Putri Zudhah (Universitas Pendidikan Ganesha, 2023)
Optimal learning conditions can be seen from the ability of teachers to manage students and teaching facilities in a pleasant atmosphere to achieve teaching goals, as well as to establish good interpersonal relationships between teachers and students and students with students. Based on, this research aims to find out the influence of teacher performance on the learning outcomes of elementary school students. Population of this study amounted to 45 people. The sample of this study was 23 people who were determined using the Randome Sampling technique learning achievement. Data were collected through questionnaires and documentation to be then analyzed using descriptive statistics, normality test, linearity test, simple linear regression test, and coefficient of determination test. The results showed that teacher performance had an influence on the learning outcome of V SD N 1 Gentan students based on t-calculated > t-table (3.902 > 2.080) and the coefficient of determination of 0.20 showing that performance was able to explain the learning outcome of students by 42% while 58% was influenced by other variables.